Three-Phase Squirrel-Cage Induction Motor Dynamic Thermal Mathematical Model - Filho, E. Ruppert; Avólio, E. [UNESP]; Riehl, R. R. [UNESP] (Institute of Electrical Engineers of Japan (IEE Japan), 1996)
An electrical and thermal mathematical dynamic model for a three-phase squirrel-cage induction motor is described to evaluate, via microcomputer, stator winding, rotor winding, stator core and rotor core instantaneous temperature rises for motors operating fed from sinusoidal and nonsinusoidal (inverter) voltage power supplies and driving continuous and intermittent load duties, including startings and brakings. It is required regular manufacturer bulletin data and also stator core, stator winding, rotor core and rotor winding masses. The model takes into account the skin effect on rotor parameters and the changings of the winding electrical resistances with the respective machine part temperatures. © 1996, The Institute of Electrical Engineers of Japan. All rights reserved.